Variation in complications and mortality following ALPPS at early-adopting centers. Issue 1 (January 2021) - Wanis, Kerollos N.; Linecker, Michael; Madenci, Arin L.; Müller, Philip C.; Nüssler, Natascha; Brusadin, Roberto; Robles-Campos, Ricardo; Hahn, Oszkar; Serenari, Matteo; Jovine, Elio; Lehwald, Nadja; Knoefel, Wolfram T.; et al.
Abstract: Background: Various, often conflicting, estimates for post-operative morbidity and mortality following ALPPS have been reported in the literature, suggesting that considerable center-level variation exists. Some of this variation may be related to center volume and experience. Methods: Using data from seventeen centers who were early adopters of the ALPPS technique, we estimated the variation, by center, in standardized 90-day mortality and comprehensive complication index (CCI) for patients treated between 2012 and 2018. Results: We estimated that center-specific 90-day mortality following treatment with ALPPS varied from 4.2% (95% CI: 0.8, 9.9) to 29.1% (95% CI: 13.9, 50.9), and that center-specific CCI following treatment with ALPPS varied from 17.0 (95% CI: 7.5, 26.5) to 49.8 (95% CI: 38.1, 61.8). Declines in estimated 90-day mortality and CCI were observed over time, and almost all individual centers followed this trend. Patients treated at centers with a higher number of ALPPS cases performed over the prior year had a lower risk of post-operative mortality. Conclusion: Despite considerable center-level variation in ALPPS outcomes, perioperative outcomes following ALPPS have improved over time and treatment at higher volume centers results in a lower risk of 90-day mortality. Morbidity and mortality remain concerningly high at some centers.